SISTEM PAKAR PEMBAGIAN WARIS MENGGUNAKAN METODE FORWARD DAN BACKWARD CHAINING - Tirkaamiasa, Taufik; Usino, Wendi (Krea-TIF: Jurnal Teknik Informatika, 2015)
Division of inheritance problems often lead to internal conflicts in the family and sometimes have to be resolved through religious courts. The science of inheritance distribution in Islam is called fara’idh, while the religious court used KHI (Compilation of Islamic Law). The small number of Muslims who understand the science fara'idh and KHI and the difficulty of getting an expert in the science, is a problem that must be solved. Offered a solution to the division of inheritance expert system using forward and backward chaining method on the basis of rules (rule-based reasoning). By using both methods can produce an expert system that is able to calculate the division of inheritance to the heir or heirs of a replacement in a single input and process. Users can also elect to use faraidh or KHI and predict the outcome.